People’s interaction and social intellect of the person - Eduard Z. Ivashkevych (Психолінгвістика, 2017)
In this article the author showed basic, fundamental features of social intellect: its continual nature; the usage of nonverbal representation of context; loss of accuracy for assessment of social conditions of verbalization of information being heard; acquiring implicit ability to subject-communication; updating personally meaningful experience.